THE IMPROVEMENT OF CORPORATE PROFITABILITY AND ITS POLICIES - Sari, Widya; Chandra, Camelia; Ciawan, William (Jurnal Aplikasi Manajemen, 2021)
With this exploration directs to explore the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on Return on Equity (ROE) to Dividend Payout Ratio (DPR) and Corporate Social Responsibility (CSR) in the Basic Industrial and Chemical sector which was listed on Indonesia Stock Exchange (IDX) 2015-2019. The population in this exploration amounted to 78 companies and the sample used was 13 companies. The method used in this research is an analysis of multiple linear regression and classical assumption test. The results showed that simultaneously CR, DER, TATO had sig effect on ROE. But, partially CR, DER had no significant effect on ROE, while TATO had sig affect ROE. Partially ROE had a negative sig effect on DPR and Corporate Social Responsibility. The result of coefficient determination with an Adjusted R 2 was 38.8% means the change of ROE had 38.8% can be explained by CR, DER, and TATO meanwhile 61.2% can be explained by the other variables outside from this study. For another analyst, it is suggested to attach other variables as reference material for further research.